SPECIAL LABOUR PROTECTION OF CERTAIN EMPLOYEE CATEGORIES - Jovanović, Predrag (Zbornik radova Pravnog fakulteta u Novom Sadu, 2016)
The employed women, the youth and the disabled enjoy special protection at work. Such a protection is stipulated by legal documents of the international and our labour law. The protection of women is provided for three reasons: the need to emancipate women and their equalisation with all the rights as men have; the protection due to women’s physical constitution; the protection due to women’s role in biological reproduction of the population (pregnancy, childbirth and maternity). The youth enjoy protection due to their young age and accordingly their adequate psychophysical and mental maturity. By youth, children and people under 18 are implied, because the minimum age for entering into labour relations is 15. This refers to the minors that are exposed to the adverse effect of the working conditions where certain more damaging and more difficult jobs can leave severe and lethal consequences on the youth’s development. The disabled are people with a reduced working ability, and thus the odds of them finding a suitable job and keep it are significantly reduced, as opposed to other people. Therefore, the reasons of their special protection lie in the need to bring them to equal terms as others to achieve their socio-economic rights at work and connected with work.